A mirror-aided laser scanning system for geometric quality inspection of side surfaces of precast concrete elements. (July 2019) - Kim, Min-Koo; Wang, Qian; Yoon, Seongheum; Sohn, Hoon
Highlights: A mirror-aided laser scanning system is developed for geometric quality inspection. The mirror can move and rotate to deflect laser beams to the target surface. Three laboratory experiments including a moving-mirror test are conducted. An average dimension estimation accuracy of 2.5 mm is achieved. Abstract: Checking the geometric quality of each precast concrete (PC) element is an important task to ensure proper assemblage of PC elements on construction sites. As manual quality inspection is time-consuming and error-prone, previous studies have deployed 3D terrestrial laser scanning to collect the scan data of PC elements for automated geometric quality inspection. However, the previous techniques have difficulties for real-world applications. To tackle the limitations, this study presents a novel mirror-aided scanning system that can scan the side surfaces of the PC element for geometric quality inspection in case the side surface is not visible to the laser scanner. To verify the proposed system, a series of laboratory experiments including moving-mirror tests are conducted. The test results show an average dimension estimation accuracy of 2.5 mm, demonstrating the potential for accurate geometric quality inspection of side surfaces of PC elements.